An investigation of the role of antenatal depression, maternal cortisol and postnatal interactive behaviour on infant neurodevelopment in the first year of life. - O' LEARY, NIAMH (Trinity College Dublin. School of Medicine. Discipline of Psychiatry, 2019)
Abstract Aims: Major Depressive Disorder (MDD) is the most prevalent psychiatric disorder during the perinatal period and can lasting adverse effects on maternal wellbeing and infant development. This aim of this thesis was to investigate the relationship between antenatal depression, maternal cortisol and postnatal interactive behaviour and infant neurodevelopment across the first year of life. Method: Three groups of pregnant women were recruited to this study; women with a current diagnosis of MDD (n=23), women with one or more previous episodes of MDD (n=34) and healthy women with no previous diagnosis of psychiatric disorder (n=43). Maternal mood and cortisol were measured during pregnancy and mothers and their infants were followed up two, six and twelve months. Maternal mood, infant neurodevelopment and mother-infant interactive behaviour were measured at each postpartum time-point. Results: No group differences were observed for infant neurodevelopment. Maternal antenatal cortisol was correlated with infant cognitive and motor development at six and twelve months respectively. Postnatal depression was associated with lower syntactical complexity in the language mothers used while speaking to their infant. Maternal interactive behaviour was associated with infant self-regulation, cognitive and motor development. Maternal behaviour moderated the relationship between antenatal cortisol and infant neurodevelopment indicating that more optimal levels of maternal interactive behaviour were associated with better infant outcomes. Conclusions: These findings suggest that MDD is not reliably associated with adverse infant outcomes or impairments within the mother-infant relationship. These results also demonstrate a 'programming' effect of antenatal cortisol on the developing fetus which has implications for infant cognitive and motor development. This study provides evidence that these adverse effects can be precluded in the context of a supportive postnatal environment.
APPROVED
Keywords: Antenatal depression; Neurodevelopment; Cortisol; Mother-infant interaction